Outsourcing, bureaucratic personnel quality and citizen satisfaction with public services. (5th February 2018) - Dahlström, Carl; Nistotskaya, Marina; Tyrberg, Maria
Abstract : This article investigates the relationships between outsourcing, bureaucratic personnel quality (BPQ) and citizen satisfaction with public services. Our baseline expectation is of a negative association between outsourcing and service quality; however, we argue that this tendency can be counteracted when the government buyer has a more competent and motivated personnel, not only in managerial positions, but across the board. Better‐educated and paid public employees are likely to have an important moderating effect on service quality through their input into quality specifications, their ability to recognize the provider's consummate or perfunctory behaviour, and their willingness to act on the observed performance. Using data from a cross‐section of Sweden's municipalities, our analysis reveals a robust association between higher levels of outsourcing and lower levels of citizen satisfaction, but the data do not provide unambiguous support for the hypothesis that the strength of this association diminishes when BPQ is higher.